Modelling of spray evaporation and penetration for alternative fuels - Azami, Muhammad Hanafi; Savill, Mark (Elsevier, 2016)
The focus of this work is on the modelling of evaporation and spray penetration for alternative fuels. The extension model approach is presented and validated for alternative fuels, namely, Kerosene (KE), Ethanol (ETH), Methanol (MTH), Microalgae biofuel (MA), Jatropha biofuel (JA), and Camelina biofuel (CA). The results for atomization and spray penetration are shown in a time variant condition. Comparisons have been made to visualize the transient behaviour of these fuels. The vapour pressure tendencies are revealed to have significant effects on the transient shape of the evaporation process. In a given time frame, ethanol fuel exhibits the highest evaporation rate and followed by methanol, other biofuels and kerosene. Ethanol also propagates the farthest distance and followed by methanol and kerosene. However, all biofuels have a shorter penetration length in the given time. These give penalty costs to biofuels emissions formation. The influences of initial conditions such as temperature and droplet velocity are also explored numerically. High initial temperature and velocity could accelerate evaporation rate. However, high initial temperature has resulted in low penetration length while high initial velocity produces contrasting results.